Preparation method and application of metal ion doped synthetic layer oxygen positive electrode material

By doping metal ions and preparing a layered oxygen positive electrode material with specific chemical formulas, the structural stability and electrochemical performance problems of O3-phase layered oxygen positive electrode material in sodium ion batteries are solved, and higher specific capacity and cycle are achieved Stability and air stability.

CN119409238AInactive Publication Date: 2025-02-11TIANJIN WASTSODIUM TECHNOLOGY RESEARCH & DEVELOPMENT CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510012197.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing O3-phase oxygen cathode material has problems such as poor structural stability, severe capacity attenuation, and poor circulation and processing performance in sodium ion batteries. After contact with air, Na+/H+ exchange occurs to generate alkaline substances, affecting battery performance. .

Method used

By mixing the nickel-ferromanganese precursor, the A-containing compound and the sodium salt in a specific molar ratio, sintering and crushing treatment, a layered oxygen positive electrode material with the chemical formula NaxAyNi0.33Fe0.33Mn0.33O2 is prepared, and the metal is doped Ions to improve the structural stability and electrochemical properties of the material.

Benefits of technology

Improve the specific capacity, structural stability and cyclic stability of the oxygen cathode material of the sodium ion battery layer, enhance the sodium ion diffusion kinetics of the material during charging and discharging, reduce the residual alkali on the material surface, improve air stability and Rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409238A_ABST
    Figure CN119409238A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a preparation method and application of a metal ion doped synthetic layer oxygen positive electrode material. The embodiment verifies that the layered oxygen positive electrode material NaxAyNi0. 33Fe0. 33Mn0. 33O2 prepared by the method provided by the invention is uniform in particle size, high in porosity, high in crystallinity and good in crystal form, and is a typical O3-phase layered oxygen positive electrode material. An embodiment verifies that the layered oxygen positive electrode material prepared by the invention has higher specific capacity, first-week coulombic efficiency and more excellent rate capability, cycling stability and air stability, and solves the problems of rapid capacity attenuation, poor rate capability and cycling stability, instability in air and the like in the charging and discharging process of the material. The method provided by the invention is simple in synthesis process and low in cost, and can meet the requirements of large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a preparation method and application of a metal ion doped synthetic layer oxygen positive electrode material. Background Art

[0002] In recent years, lithium resources have been increasingly scarce worldwide. Sodium-ion batteries have shown broad application prospects due to the abundant sodium resources in the earth's crust, low price, high safety and other advantages. Sodium-ion battery positive electrode materials are mainly divided into several types, such as layered oxides, Prussian blue compounds and polyanion compounds. They have their own characteristics in terms of energy density, cycle stability, production cost and environmental friendliness. Among them, layered oxygen positive electrode materials are mainly divided into P2, P3, O2 and O3 phases, of which P2 and O3 phase structures are the most common. Due to the high theoretical capacity of O3 phase layered oxygen materials, they have attracted widespread attention, but there are still many shortcomings that are difficult to overcome, which seriously hinder the commercial application of layered oxygen positive electrode materials. For example, Na + Complex phase changes often occur during the embedding and de-embedding process, resulting in poor structural stability, severe capacity attenuation, poor cycle performance and processing performance of the material. In addition, Na+ will occur on the surface of the material after contact with carbon dioxide and water in the air. + / H + The exchange produces a series of alkaline substances such as NaOH, and carbon dioxide will be absorbed by some strong alkaline substances to form other by-products such as carbonates, which will block the sodium ion transmission channel and collapse the crystal structure during the charge and discharge process of the battery, causing the electrochemical properties of the material to decline rapidly, while increasing the difficulty and cost of transporting the materials.

[0003] Therefore, in response to the above problems, researchers can improve the electrochemical performance of sodium-ion battery layered oxygen cathode materials by means of coating, bulk phase doping and other means. The existing technology performs multi-dimensional modification on the O3 phase layered oxygen cathode material. For example, CN116682937A forms a hydrophobic organic coating on the surface of the layered oxide, which can protect the O3 phase layered oxide material from phase change side reactions, improve air stability, and thus improve cycle performance; CN115692670A constructs a sodium-poor rock salt phase on the surface of the O3 phase. The sodium-poor phase structure acts as a coating layer, isolating the electrolyte while reducing the surface activity of the cathode material and improving the stability of the layered oxide material when in contact with air. Although coating the surface of the layered oxygen material with an organic layer and constructing a sodium-poor rock salt phase can achieve isolation from the air, the coating layer is thick, which reduces the ion conduction rate, making it difficult to improve the material's charge and discharge specific capacity and rate performance. CN118125517A synthesizes a positive electrode material of layered oxide composite carbon nanotubes by a spray drying method, which solves the problems of poor rate performance and rapid capacity decay of existing layered metal oxide positive electrode materials; however, its synthesis process is complicated, the cost is high, and it is difficult to achieve mass production. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a metal ion-doped synthetic layered oxygen positive electrode material and its application, so that the sodium ion battery positive electrode material has excellent charge and discharge gram capacity, rate performance and cycle stability, thereby improving the application advantages of sodium ion batteries.

[0005] The present invention provides a method for preparing a metal ion doped synthetic layer oxygen positive electrode material, the method comprising the following steps: A nickel-manganese-iron precursor, a compound containing element A and a sodium salt are mixed in a molar ratio of NFM:A:Na=1:0.01-0.05:0.8-1.2, and ground into a dry powder state to obtain a mixed material; the element A is an element having an ion radius greater than or equal to 0.06 nm; (2) sintering the mixture obtained in step (1) in a dry air atmosphere to obtain a sintered product; (3) The sintered product obtained in step (2) is crushed, pulverized and passed through a 300-mesh sieve to obtain a product having a chemical formula of Na x A y Ni 0.33 Fe 0.33 Mn 0.33 O 2 , layered oxygen cathode material with particle size D50 = 4μm~8μm, where 0.8≤x≤1.1, 0.01≤y≤0.05; Preferably, the structural formula of the nickel-manganese-iron precursor is Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 ; The particle size is 3μm~20μm.

[0006] Preferably, the A element is one or more of Cu, Mg, K, Ca, and Ti.

[0007] Preferably, the compound containing element A has a purity of ≥99.5% and a particle size of 3 μm to 20 μm.

[0008] Preferably, the sodium salt is sodium carbonate and / or sodium bicarbonate.

[0009] Preferably, the purity of the sodium salt is ≥99.5%, and the particle size is 3 μm to 20 μm.

[0010] Preferably, the humidity of the dry air is ≤40%.

[0011] Preferably, the grinding includes a first grinding and a second grinding, wherein the first grinding is: adding anhydrous ethanol in a mass ratio of anhydrous ethanol to the material of 2:5 for wet grinding, and grinding to a dry powder state; the second grinding is: adding anhydrous ethanol in a mass ratio of anhydrous ethanol to the material of 2:5 for wet grinding, and grinding to a dry powder state.

[0012] Preferably, the sintering temperature is 800° C. to 1000° C., the sintering time is 8 h to 15 h, and the sintering heating rate is 2° C. / min to 5° C. / min.

[0013] The present invention also provides the application of the method described in the above technical solution in the preparation of sodium ion batteries.

[0014] Beneficial effects of the present invention: 1. The present invention provides a method for preparing a metal ion doped synthetic layer oxygen positive electrode material, which can destroy Na + / Na + There is a strong interaction between them, and the metal ions can play a supporting role in the transition metal layer, inhibiting the Na + The orderly arrangement of the vacancies reduces the collapse of the crystal structure caused by the irreversible phase change. Therefore, the material synthesized by the method provided by the present invention has a higher specific capacity and better structural stability and cycle stability.

[0015] 2. The present invention improves the sodium ion diffusion kinetics of the obtained sodium ion battery layer oxygen positive electrode material during the charge and discharge process by doping a specific proportion of metal ions for specific sintering, thereby increasing the sodium ion deintercalation rate and reducing the residual alkali on the surface of the material. While isolating the electrolyte, the stability of the layer oxygen material when in contact with air is improved. It has been verified by the examples that the layer oxygen positive electrode material prepared by the method provided by the present invention has a first charge and discharge specific capacity of 151.8mAh / g and 140.3mAh / g in the voltage range of 2~4V, and the first coulomb efficiency is 92.4%. The discharge specific capacity can still reach 129.1mAh / g and 110.5mAh / g at 1C and 5C rates. After 100 cycles at 1C rate, the capacity retention rate is above 92%. It can be seen that the layer oxygen positive electrode material prepared by the method provided by the present invention has higher rate performance and air stability.

[0016] 3. The present invention adopts a solid phase method to synthesize layered oxygen positive electrode materials. After mixing a nickel-manganese-iron precursor with a sodium source and a compound containing the element A, the mixture is sintered in a dry air atmosphere. The resulting product can be crushed, pulverized, sifted and other steps to obtain a layered oxygen positive electrode material with excellent electrochemical properties. The synthesis process is simple, low-cost and has a wide range of raw material choices. It is most likely to follow the lithium-ion battery production process and quickly achieve commercialization.

[0017] 4. The layered oxygen positive electrode material synthesized by the method provided by the present invention has uniform particle size, high crystallinity, no obvious impurities, stable structure, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0019] Figure 1 This is a SEM image of the layered oxygen cathode material prepared in Example 1; Figure 2 XRD pattern of the layered oxygen cathode material prepared in Example 1; Figure 3 This is the first week charge and discharge curve of the middle layer oxygen positive electrode material in Example 1; Figure 4 This is a rate performance diagram of the middle layer oxygen positive electrode material in Example 1; Figure 5 This is the cycle performance diagram of the middle layer oxygen positive electrode material in Example 1. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a metal ion doped synthetic layer oxygen positive electrode material, the method comprising the following steps: (1) Mixing a nickel-manganese-iron precursor, a compound containing element A and a sodium salt according to a molar ratio of NFM:A:Na=1:0.01-0.05:0.8-1.2, grinding to a dry powder state, and obtaining a mixed material; the element A is an element having an ion radius greater than or equal to 0.06 nm; (2) sintering the mixture obtained in step (1) in a dry air atmosphere to obtain a sintered product; (3) The sintered product obtained in step (2) is crushed, pulverized and passed through a 300-mesh sieve to obtain a product having a chemical formula of Na x A y Ni 0.33 Fe 0.33 Mn 0.33 O 2 , layered oxygen cathode material with particle size D50 = 4μm~8μm, where 0.8≤x≤1.1, 0.01≤y≤0.05; The present invention firstly mixes a nickel-manganese-iron precursor, a compound containing an A element and a sodium salt according to a mass ratio of NFM:A:Na=1:0.01-0.05:0.8-1.2, and grinds the mixture into a dry powder state to obtain a mixed material.

[0021] In the present invention, the structural formula of the nickel-manganese-iron precursor is preferably Ni 0.33 Fe 0.33 Mn 0.33 (OH) 2 , the particle size is preferably 3μm~20μm; the A element is an element with an ionic radius ≥0.06nm, and is further preferably one or more of Cu, Mg, K, Ca, and Ti; the purity of the compound containing the A element is preferably ≥99.5%, and the particle size is preferably 3μm~20μm; the sodium salt is sodium carbonate and / or sodium bicarbonate; the purity of the sodium salt is preferably ≥99.5%, and the particle size is preferably 3μm~20μm. The present invention defines the A element as an element with an ionic radius ≥0.06nm, and metal ion doping can destroy Na + / Na + There is a strong interaction between them, and the metal ions can play a supporting role in the transition metal layer, inhibiting the Na + / vacancies are arranged in an orderly manner, reducing the collapse of the crystal structure caused by irreversible phase change; the present invention can increase the surface area of ​​the material by limiting the particle size of each raw material, thereby improving the kinetics of its electrochemical reaction. In addition, the control of particle size helps to optimize the synthesis process of the material and reduce the CO2 in the material and the environment. 2 / The adverse chemical reaction between water and the atmosphere improves the air stability of the material, making the composition and structure of the material more uniform, thereby improving the overall performance of the material.

[0022] In the present invention, the grinding preferably includes a first grinding and a second grinding, and the first grinding is preferably: adding anhydrous ethanol according to a mass ratio of anhydrous ethanol to the material of 2:5 for wet grinding, grinding to a dry powder state; the second grinding is preferably: adding anhydrous ethanol according to a mass ratio of anhydrous ethanol to the material of 2:5 for wet grinding, grinding to a dry powder state. In order to make different materials mix more evenly, the present invention selects to perform two grindings; wet grinding can make the materials mix more evenly, and the use of anhydrous ethanol is more volatile, which prevents ethanol from being adsorbed on the surface of the material and prevents the materials from sticking.

[0023] After obtaining the mixed material, the present invention sintered the mixed material in a dry air atmosphere to obtain a sintered product, and the sintered product was crushed, pulverized and passed through a 300-mesh sieve to obtain a chemical formula of Na x A y Ni 0.33 Fe 0.33 Mn 0.33 O 2 , layered oxygen positive electrode material with particle size D50=4μm~8μm.

[0024] In the present invention, the humidity of the dry air is preferably ≤40%, more preferably 20%; the sintering temperature of the present invention is preferably 800℃~1000℃, further preferably 800℃~900℃, more preferably 900℃; the sintering time is preferably 8h~15h, more preferably 8h; the sintering heating rate is preferably 2℃ / min~5℃ / min, more preferably 3℃ / min. In the present invention, it is preferred to cool the mixed material to room temperature and then take it out after the sintering to obtain a sintered product; the cooling rate is preferably 5℃ / min. The present invention performs sintering in dry air, which can effectively reduce side reactions and improve the air stability of the material; adjusting the cooling rate helps to obtain a better crystal structure and higher crystallinity, thereby improving the structural stability of the material.

[0025] The present invention also provides the application of the method described in the above technical solution in the preparation of sodium ion batteries.

[0026] In the present invention, the application is preferably to prepare a layered oxygen positive electrode material using the method described in the above technical scheme, and then assemble a button battery using the prepared layered oxygen positive electrode material; the preparation method of the button battery is preferably: mixing the layered oxygen positive electrode material, conductive carbon black and PVDF in a mass ratio of 9.4:0.3:0.3, adding N-methylpyrrolidone solution to prepare an active material slurry, and then evenly coating the slurry on an aluminum foil, vacuum drying at 110°C for 8h, rolling and cutting to obtain the positive electrode sheet used, using a metal sodium sheet as a counter electrode and glass fiber as a diaphragm, and assembling in an argon-filled glove box to obtain a button battery.

[0027] In order to further illustrate the present invention, the preparation method and application of a metal ion doped synthetic layer oxygen positive electrode material provided by the present invention are described in detail below in combination with the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0028] Example 1 The chemical formula is Na 1.1 Ni 0.33 Fe 0.33 Mn 0.33 Cu 0.01 Ti 0.04 O 2 The sodium ion battery layered oxide positive electrode material is prepared as follows: (1) Add nickel-manganese-iron precursor, copper oxide, titanium dioxide, and sodium carbonate in a molar ratio of 1:0.01:0.04:1.1 into an agate mortar and grind for the first time: add 20 mL of anhydrous ethanol for wet grinding until it is in a dry powder state; then, grind for the second time: add 20 mL of anhydrous ethanol again for wet grinding until it is in a dry powder state to obtain a mixed material. The structural formula of the nickel-manganese-iron precursor is Ni0.33 Fe 0.33 Mn 0.33 (OH) 2 , particle size D50=6.1μm, sodium carbonate particle size D50=12μm, purity ≥99.5%.

[0029] (2) The mixture obtained in step (1) is calcined in a dry air atmosphere (humidity 20%): the temperature is increased to 900°C at a heating rate of 3°C / min, kept at that temperature for 8 hours, and then cooled to room temperature at a cooling rate of 5°C / min, and then taken out to obtain a primary sintered product.

[0030] (3) The sintered product obtained in step (2) is crushed, pulverized and passed through a 300-mesh sieve to obtain a layered oxygen positive electrode material with a particle size of D50 = 6.5 μm.

[0031] Example 2 The same as Example 1, except that the chemical formula of the sodium ion battery layered oxide positive electrode material is Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 Cu 0.01 Ti 0.04 O 2 The molar ratio of nickel-manganese-iron precursor, copper oxide, titanium dioxide and sodium carbonate is 1:0.01:0.04:0.9.

[0032] Comparative Example 1 The same as Example 1, the only difference is that the calcination conditions in step (2) are: heating to 800°C at a heating rate of 3°C / min, keeping the temperature for 6 hours, and then cooling to room temperature at a cooling rate of 5°C / min before taking out.

[0033] Comparative Example 2 The same as Example 1, the only difference is that the calcination conditions in step (2) are: heating to 1100°C at a heating rate of 3°C / min, keeping the temperature for 6 hours, and then cooling to room temperature at a cooling rate of 5°C / min before taking out.

[0034] Comparative Example 3 The same as Example 1, except that the chemical formula of the sodium ion battery layered oxide positive electrode material is Na 1.25 Ni 0.33 Fe 0.33 Mn 0.33 Cu 0.01 Ti 0.04 O 2 The mass ratio of nickel-manganese-iron precursor, copper oxide, titanium dioxide and sodium carbonate is 1:0.01:0.04:1.25.

[0035] Comparative Example 4 The same as Example 1, except that the chemical formula of the sodium ion battery layered oxide positive electrode material is Na 1.3 Ni 0.33 Fe 0.33 Mn 0.33 Cu 0.01 Ti 0.04 O 2 The mass ratio of nickel-manganese-iron precursor, copper oxide, titanium dioxide and sodium carbonate is 1:0.01:0.04:1.3.

[0036] Test Example 1 Button cells were prepared using the layered oxygen cathode materials prepared in Example 1, Example 2, and Comparative Examples 1 to 4, respectively: layered oxygen cathode material, conductive carbon black, and PVDF were mixed in a mass ratio of 9.4:0.3:0.3, and N-methylpyrrolidone solution was added to prepare an active material slurry, which was then uniformly coated on an aluminum foil, vacuum dried at 110° C. for 8 h, and the cathode electrode sheet was obtained by rolling and cutting, a metal sodium sheet was used as a counter electrode, and a glass fiber was used as a diaphragm, and the button cells were assembled in an argon-filled glove box to obtain the button cells, and then the electrochemical performance was tested. The results are shown in Tables 1 and Figure 1~Figure 5 As shown, the charge and discharge voltage range of the electrochemical performance test is: 2~4.0V; the charge and discharge rate in the first week: 0.1C; the charge and discharge cycle rate: 1C; the number of charge and discharge cycles: 100 weeks; the charge and discharge test environment: temperature is 25℃, humidity is 10%.

[0037] Table 1 Electrochemical performance test data of sodium ion battery layer oxygen positive electrode material examples and comparative examples

[0038] The difference between Example 1 of the present invention and Comparative Examples 1 and 2 is that the material preparation methods are different. It can be seen from the data in Table 1 that the sintering temperature in the preparation process is too high or the sintering time is too low, which affects the growth of the crystal, resulting in lower discharge capacity and first-week efficiency than Example 1; the difference between Example 1 and Comparative Examples 3 and 4 is that the chemical formula of the synthesized layered oxygen positive electrode material is different. It can be seen from the data in Table 1 that too much sodium carbonate is added during the synthesis process, which will affect the material capacity and make its first-week efficiency low.

[0039] It can be concluded from the above embodiments that doping with transition metal ions can form a supporting structure in the transition metal layer through its internal synergistic effect, thereby inhibiting the Na + / Orderly arrangement of vacancies improves ion transmission rate and reduces structural collapse of materials during charge and discharge cycles; the sodium ion battery layer oxygen positive electrode material obtained by doping a certain proportion of transition metal elements and sintering at a special temperature in a dry air atmosphere has excellent first-week charge and discharge specific capacity, first-week efficiency, and capacity retention rate. In addition, the material preparation process of the present invention is simple and low-cost, which is conducive to industrial production.

[0040] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a metal ion doped synthetic layered oxygen cathode material, characterized in that: The method comprises the following steps: A nickel-manganese-iron precursor, a compound containing element A and a sodium salt are mixed in a molar ratio of NFM:A:Na=1:0.01-0.05:0.8-1.2, and ground into a dry powder state to obtain a mixed material; the element A is an element having an ion radius of ≥0.06 nm; (2) sintering the mixture obtained in step (1) in a dry air atmosphere to obtain a sintered product; (3) The sintered product obtained in step (2) is crushed, pulverized and passed through a 300-mesh sieve to obtain a product having a chemical formula of Na x A y Ni 0.33 Fe 0.33 Mn 0.33 O2, layered oxygen positive electrode material with particle size D50=4μm~8μm, where 0.8≤x≤1.1, 0.01≤y≤0.

05.

2. The method according to claim 1, characterized in that The structural formula of the nickel-manganese-iron precursor is Ni 0.33 Fe 0.33 Mn 0.33 (OH)2; particle size is 3μm~20μm.

3. The method according to claim 1, characterized in that The A element is one or more of Cu, Mg, K, Ca, and Ti.

4. The method according to claim 1 or 3, characterized in that: The purity of the compound containing element A is ≥99.5%, and the particle size is 3 μm-20 μm.

5. The method according to claim 1, characterized in that The sodium salt is sodium carbonate and / or sodium bicarbonate.

6. The method according to claim 1, characterized in that The purity of the sodium salt is ≥99.5%, and the particle size is 3 μm to 20 μm.

7. The method according to claim 1, characterized in that The humidity of the dry air is ≤40%.

8. The method according to claim 1, characterized in that The grinding includes a first grinding and a second grinding. The first grinding is: adding anhydrous ethanol according to a mass ratio of anhydrous ethanol to the material of 2:5 for wet grinding, and grinding to a dry powder state; the second grinding is: adding anhydrous ethanol according to a mass ratio of anhydrous ethanol to the material of 2:5 for wet grinding, and grinding to a dry powder state.

9. The method according to claim 1, characterized in that: The sintering temperature is 800° C. to 1000° C., the sintering time is 8 h to 15 h, and the sintering heating rate is 2° C. / min to 5° C. / min.

10. Use of the method according to any one of claims 1 to 9 in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • Single-crystal positive electrode active material for sodium ion battery and preparation method and application of single-crystal positive electrode active material

    CN115458732A

  • Inert metal ion doped nickel iron sodium manganate ternary positive electrode material and preparation method thereof

    CN116646514A

  • Air-stable sodium battery positive electrode material as well as preparation method and application thereof

    CN118231617A

  • Calcium ion doped modified sodium ion positive electrode material and preparation method thereof, positive electrode plate and half cell

    CN119230834A

  • Layered oxide and preparation method thereof, positive electrode sheet, secondary battery, battery module, battery pack and electrical apparatus

    US20240088376A1